Transgenerational effects of obesogenic diets in rodents: A meta‐analysis. (30th September 2021) - Anwer, Hamza; Morris, Margaret J.; Noble, Daniel W. A.; Nakagawa, Shinichi; Lagisz, Malgorzata
Summary: Obesity is a major health condition that affects millions worldwide. There is an increased interest in understanding the adverse outcomes associated with obesogenic diets. A multitude of studies have investigated the transgenerational impacts of maternal and parental obesogenic diets on subsequent generations of offspring, but results have largely been mixed. We conducted a systematic review and meta‐analysis on rodent studies to elucidate how obesogenic diets impact the mean and variance of grand‐offspring traits. Our study focused on transgenerational effects (i.e., F2 and F3 generations) in one‐off and multigenerational exposure studies. From 33 included articles, we obtained 407 effect sizes representing pairwise comparisons of control and treatment grand‐offspring groups pertaining to measures of body weight, adiposity, glucose, insulin, leptin, and triglycerides. We found evidence that male and female grand‐offspring descended from grandparents exposed to an obesogenic diet displayed phenotypes consistent with metabolic syndrome, especially in cases where the obesogenic diet was continued across generations. Further, we found stronger evidence for the effects of grand‐maternal than grand‐paternal exposure on grand‐offspring traits. A high‐fat diet in one‐off exposure studies did not seem to impact phenotypic variation, whereas in multigenerational exposure studies it reduced variation in several traits.